Human capital and growth: Specification matters - Uwe Sunde; Thomas Vischer (Institute for the Study of Labor (IZA), 2011)
This paper suggests that the weak empirical effect of human capital on growth in existing cross-country studies is partly the result of an inappropriate specification that does not account for the different channels through which human capital affects growth. A systematic replication of earlier results from the literature shows that both, initial levels and changes in human capital, have positive growth effects, while in isolation, each channel often appears insignificant. Moreover, the effects are heterogeneous across countries with different levels of development. The results suggest that the effect of human capital is likely to be underestimated in empirical specifications that do not account for both channels. This study therefore complements alternative explanations for the weak growth effects of human capital based on outlier observations and measurement issues.
urn:nbn:de:101:1-201110263293
Keywords: O47; O11; O15; E24; 330; human capital; growth regressions; specification; Humankapital; Wirtschaftswachstum; Regression; Schätzung; Welt